Neuropsychological factors and cognitive processes in children with writing difficulties and without writing difficulties - Canales, Ricardo C. (2013)
This research sought to contribute to the knowledge of the differences in the level of development of neuropsychological factors and cognitive processes in children with and without writing difficulties. Similarly, we wanted to see if there was an association between neuropsychological factors and processes involved in writing. Descriptive design was causal comparative, examining 80 children in third through sixth grade, studying in state schools of Callao using EPRE Test (Velarde, Canales, Melendez & Lingán, 2014), Child Neuropsychological Diagnostic Test Luria-DNI Test and Wechsler intelligence: WISC-IV. The results showed significant differences in all neuropsychological factors favoring the group without writing difficulties. Also, no relationship between most neuropsychological factors and psychological processes involved in writing. The instruments demonstrated their validity and usefulness.